(3eNJUQ GdGSJjYGH aj eYQaI GdCUMGHs - (3Ydj Hf eMeO Hf YHO GdQMef GdMSjfjs; (3GHf YHO GdHQ , CHh YeQ jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj,J (B463 (3g` s
(3ChdgG (B:s
(3Chdg eHJhQ , hjHOC GdehLhO efg CKfGA JQLeI (B" (3SdeGf GdaGQSi(B" (3QVi Gddg Yfg s
(3BNQgG (B:s
(3gPG BNQ eG dNUJg hGNJUQJg ef cJGH GdGSJjYGH hCfG GdYHO GdePfH Ydi Hf eMeO Hf YHO GdQMef GdMSjfi ai ChGNQ QHjY GdKGfi SfI (B912 s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B240 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B315s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B369 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs